Identification of differentially expressed genes in the oviduct of two rabbit lines divergently selected for uterine capacity using suppression subtractive hybridization. (9th November 2012) - Ballester, M.; Castelló, A.; Peiró, R.; Argente, M. J.; Santacreu, M. A.; Folch, J. M.
Summary Suppressive subtractive hybridization libraries from oviduct at 62 h post‐mating of two lines of rabbits divergently selected for uterine capacity were generated to identify differentially expressed genes. A total of 438 singletons and 126 contigs were obtained by cluster assembly and sequence alignment of 704 expressed sequence tags (ESTs), of which 54% showed homology to known proteins of the non‐redundant NCBI databases. Differential screening by dot blot validated 71 ESTs, of which 47 showed similarity to known genes. Transcripts of genes were functionally annotated in the molecular function and the biological process gene ontology categories using the blast2go software and were assigned to reproductive developmental process, immune response, amino acid metabolism and degradation, response to stress and apoptosis terms. Finally, three interesting genes, PGR, HSD17B4 and ERO1L, were identified as overexpressed in the low line using RT‐qPCR. Our study provides a list of candidate genes that can be useful to understanding the molecular mechanisms underlying the phenotypic differences observed in early embryo survival and development traits.